Posmertnoe donorstvo : problemy pravogo regulirovaniâ - Kapustina, Mariâ Aleksandrovna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
According to Russian Law «On transplantation of organs and (or) human tissue» there is a presumption of consent to donation ex mortuo (model «uncalled consent») in Russian Federation. Transplantation should be based on respect for human rights, the interests of the person should prevail over the interests of society or science. Purpose of legal regulation: the legal guarantee of the right to be free to dispose of her/his body after death, and (or) the state of human rights in the provision of medical care by post mortem transplantation?
Keywords: prawo; regulacje prawne; prawa człowieka; transplantacja; narządy ludzkie